Key Discourses of Turkish Eurasianism and Their Impact on Turkey’s Foreign Policy - Ғ.Б. Жұматай; А.С. Ысқақ (Halyk̦aralyk̦ k̦atynastar ža̋ne halyk̦aralyk̦ k̦u̇k̦yk̦ seriâsì)
The paper sheds light on Turkish Eurasianism (Avrasyacılık), identifying various versions and traditions of Eurasianism in Turkey. Analyzing conceptual, theoretical, and ideological underpinnings of different varieties of Turkish Eurasianism, we will look into how they affect Turkey’s foreign policy course, especially in steering the country away from the conventional unidimensional pro-Western orientation and shifting it towards greater Eurasia through building a strategic alliance with states in Eurasia. The results of our research have shown that all varieties of Turkish Eurasianism to a certain extent are anti-imperialist, anti-Western and counter-hegemonic discourses, which place greater emphasis upon Turkey’s strategic independence from the West and its shift towards Eurasia. Yet it has been also revealed that despite their forceful advocacy for a deep paradigm shift and foreign policy change by reorienting from pro-Western to pro-Eurasian policy, as political forces Turkish Eurasianists are not powerful and their influence in informing and guiding Turkish foreign policy is rather marginal and limited. It is evident that despite the ruling AKP and its leaders occasionally ally themselves with Turkish Eurasianists, Turkey’s foreign policy is based on realism and pragmatism, rather than sentimentalism and ideology. From this standpoint, it would be premature to talk about the Turkish disengagement from the West and its pivot to Eurasia, as Ankara’s security and foreign policy are closely intertwined with the West and deeply embedded within the Western security system.